PENDIDIKAN POLITIK DALAM DEMOKRATISASI - Sukarno, Bedjo (UNIVERSITAS SLAMET RIYADI, 2011)
Abstract: Political education which is done deliberately and with purpose to give understanding to people about the political position and the rights and obligations as citizens. It is also necessary democratization of the human person, and the democratization of institutions and government bureaucracy, so that all means are not running an authoritarian and arbitrary executions. Bedjo Sukarno â€“ FISIPÂ Unisri Key Word :Â Political education, democratization